Structural Analysis and the Canadian Constitution - Rowe, Malcom; Oza, Manish (The Canadian Bar Review, 2023)
This article is about structural analysis in Canadian constitutional law. Structural analysis is a methodology for identifying unwritten components of the constitution and giving them effect. These unwritten components—Parliamentary privilege, Crown prerogative, constitutional conventions and underlying constitutional principles—pertain to the basic institutions of the state and the norms that govern their operations and relations. We explain how structural analysis operates and show that it is essential to discerning and applying the unwritten constitution.